Determination of fire-access zones along road networks in fire-sensitive forests - Akay, Abdullah Emin; Wing, Michael G.; Zengin, Murat; Kose, Osman (Northeast Forestry Univ, 2017)
Wild forest fires are one of the greatest environmental disasters affecting forest resources. Along the coastal zone of the Mediterranean region in Turkey, forested areas are classified as first-degree, fire-sensitive areas. Every year, thousands of hectares of forests have been destroyed in Turkey. In this study, fire-access zones were determined in the Mediterranean forests of Turkey, by utilizing geographic information systems (GIS) technology. The effective reach distance of fire hoses from both sides of roads was considered in order to delineate fire-access zones. The effective reach distance can vary based on the technical capabilities and hydraulic capacity of fire trucks (minimum and maximum pressures on water pump); terrain structures (uphill, downhill and flat); and ground slope. These factors and their influences were studied in fire sensitive forest areas located in the eastern Mediterranean city of KahramanmaraAY in Turkey. First, terrain structures on both sides of the road network and ground-slope classes were determined based on GIS data layers. Then, fire access zones were delineated according to water pressure data, terrain structures, and ground-slope classes. The results indicated that 69.30 % of the forested areas were within the fire-access zones, while the rest of the forest was out of reach the fire hoses. The accessible areas were also calculated for forested areas with different fire-sensitivity degrees. The accessible areas were 69.59, 69.96, and 67.16 % for the forested areas that are sensitive to fires at the first, second, and third degrees, respectively. This finding has implications for the monitoring and management of fire threats in areas outside of the reach distance. The outside areas should receive extra attention and monitoring during the fire season so that fires are detected ahead of time and management has sufficient time to react. Besides, new roads should be considered for these areas in order to access more lands in a shorter amount of time.
Akay, Abdullah Emin/0000-0001-6558-9029
Keywords: Fire equipment; Fire protection areas; Forest fires; Terrain structures